Future Teachers and Construction of Professional Identity: A Psychosocial Look at the Processes that Come into Play during Preservice Practice Teaching - César Sánchez Olavarría (Universidad Autónoma de Baja California, 2012)
The present study examines the occupational and generational mobility of communication studies graduates from the Universidad del Altiplano [University of the Altiplano], located in the state of Tlaxcala, Mexico, taking into account their date of graduation and gender. The analysis of the information, from a study of career paths, identified four types of mobility: intragenerational mobility, intergenerational mobility, internal mobility and external mobility. The results allow us to observe that most of the graduates with a major in communication sciences have had little mobility. However, occupational mobility is greater in graduates who have spent more time in the job market, particularly women. Meanwhile, generational mobility shows the importance of women for family support and highlights the differences between parents and children in level of academic training, even though their incomes are similar.